الحساسية الفيزيولوجية للتنبيه الكهربائي (الفسفين) في حالات اعتلال الشبكية السكري - تعتاع عبد القادر (Latakia University Journal -Medical Sciences Series, 2019)
قياس عتبة الحساسية الكهربائية الفيزيولوجية( الفسفين) في مراحل اعتلال الشبكية السكري باستخدام جهاز التنبيه الكهربائي للعين KNS2-90 (الفسفين). تمت هذه الدراسة في المشفى الجامعي وفي الوحدة المهنية العينية. لقد أظهرت الدراسة باستخدام الجهاز المقترح أن عتبة الحساسية الكهربائية بالفسفين تزداد مع تقدم اعتلال الشبكية السكري اعتباراً من (56.8 %) عن الطبيعي لدى مرضى اعتلال الشبكية السكري البسيط و( 282 %) ما قبل التكاثري و(466 %) التكاثري و(642.3 %) المتقدم و( 998.1%) عند انفصال الشبكية الشدي الحديث وغيابها عند انفصال الشبكية الشدي القديم0. وهكذا فإن دراسة عتبة الحساسية الكهربائية بالفسفين تعتبر قيمة علمية وعملية ثمينة إضافية في تشخيص اعتلال الشبكية السكري . Measurement of the threshold of physiological electrical sensitivity (phosphen) for diabetic retinopathy stages using eye electrical stimulating device KNS2-90(phosphen) was done in the professional eye unit, Al-Assad University Hospital. The study with the suggested device showed that the electrical sensitivity increases with the progression in diabetic retinopathy with (56.8%) above normal in background diabetic retinopathy, (282%) in preproliferative, (466%) in proliferative, (642.3%) in advanced, (998.1%) in recent tractional retinal detchament, and its absence in old tractional retinal detchament. Thus, the study of the threshold of physiological electrical sensitivity with (phosphen) is considered an additional practical and scientific value in the diagnosis of diabetic retinopathy.